Promocja czytelnictwa dzieci i młodzieży przez Wojewódzką Bibliotekę Publiczną – Książnicę Kopernikańską w Toruniu w latach 80. XX wieku - Lewandowska, Martyna (Biuletyn Historii Wychowania, 2020)
The article presents activities undertaken by a Public Provincial Library – the Copernicus Library in Toruń in the field of promoting readership among children and adolescents in the 1980s. The author describes the situation of libraries after WWII and the role of librarians, emphasizing the educational aspect of their work. In addition, she recreates the course of seminars organised for librarians from children’s libraries, the curiculum of which included academic lectures including lectures on authors of books for children, an analysis of the status of readership and libraries and a discussion of the latest developments. The text includes a description of popularizing activities and initiatives. Cyclical library lessons and thematic projects like holiday and summer campaigns, are also described. The article is based mainly on historical source materials stored in the Archives of the Public Library and the State Archives in Toruń. They include documents relating to the institution, i.e. reports, characteristics of the directions of library development for selected years, as well as materials documenting library events and happenings.